Use of biogenic silver nanoparticles on the cathode to improve bioelectricity production in microbial fuel cells - Elkhrachy, Ismail; Singh, Vandana; Kumar, Ankit; Roy, Arpita; Abbas, Mohamed; Gacem, Amel; Alam, Mir Waqas; Yadav, Krishna Kumar; Verma, Devvret; Jeon, Byong-Hun; Park, Hyun-Kyung (Frontiers in Chemistry, 2023)
Current research in Microbial Fuel Cells (MFCs) has been focused on the production of costeffective high-performance electrodes and catalysts. The present study focuses on the synthesis of silver nanoparticles (AgNpsAgNPs) by Pseudomonas sp. and evaluate their role as an oxygen reduction reaction (ORR) catalyst in an MFC. Biogenic AgNpsAgNPs were synthesized from Pseudomonas aeruginosa via facile hydrothermal synthesis. The physio-chemical characterization of the Biogenic AgNpsAgNPs were conducted via Scanning electron microscopy (SEM), X-ray diffraction (XRD), and UVvisible spectrum analysis. SEM micrographs show a spherical cluster of AgNpsAgNPs of 20-100 nm in size. The oxygen reduction reaction (ORR) ability of the Biogenic AgNpsAgNPs was studied using cyclic voltammetry (CV). The oxygen reduction peaks were observed at 0.43V, 0.42V, 0.410V, and 0.39V. Different concentrations of Biogenic Formatted: Numbering: Continuous AgNpsAgNPs (0.25 to 1.0 mg/cm 2 ) were used as ORR catalyst at the cathode in the MFC. A steady increase was observed in the power production for increasing concentrations of Biogenic AgNpsAgNPs. Biogenic AgNpsAgNPs with a loading of 1.0 mg/cm 2 exhibited the highest power density (PDmax) of 4.70 W/m 3 , which was approximately 26.30% higher than the PDmax of loading 0.25 mg/cm 2 . The highest COD removal and Coulombic efficiency (CE) was also observed in Biogenic AgNpsAgNPs of loading 1.0 mg/cm 2 (83.8% and 11.7% respectively). However, the opposite trend was observed in the internal resistance of the MFC. The lowest internal resistance was observed in a loading of 1.0 mg/cm 2 (11.7Ω), which is attributeds to high oxygen reduction kinetics at the surface of the cathode by Biogenic AgNpsAgNPs. The results of this study concludes the ability of Biogenic AgNpsAgNPs as a cost-effective, high-performance ORR catalyst in MFC.